Geographical Information System Tool Monitoring the Environmental Impact of Tangier Industrial Zones - Sebbah, Boutaina; Wahbi, Miriam; Maâtouk, Mustapha (Transactions on Engineering and Computing Sciences, 2017)
Tangier city is classified as Moroccan second economic center after Casablanca, with three classical industrial zones and two free zones. This industrial activity is expected to increase in the next few years, especially with the implementation of new industrial areas such as “Tangier Automotive City”. Although this intense manufacturing activity is essential for the city development, it has also a direct impact on the environment; one of the major changes caused by the industrial activity is the rising of surface temperatures in industrial zones compared to their surrounding areas. This study retrieves Land Surface Temperature (LST), from three different Landsat sensors (i.e. TM, ETM+ and OLI-TIRS), using remote sensing algorithms (e.g. Land Surface Temperature, etc.) and a semi-Automatic Classification algorithm, in order to detect temperature variation in Tangier industrial areas during summer months over period between 2000 and 2016. Results show, that the industrial zones in Tangier city (TFZ and Industrial zone of Meghogha) appear 5°C warmer than their surroundings areas, with the presence of major plants that have the highest temperature values comparing to other plants such as (YAZAKI Morocco, S.E.B.N and Delphi Packard Electric) in TFZ and (Jacob Delafon) in Meghogha industrial zone.